Advanced Type-2 fuzzy logic–based pitch-angle control strategy for wind energy system. Issue 1 (February 2020) - Naik, Kanasottu Anil; Gupta, Chandra Prakash; Fernandez, Eugene
In general, pitch-angle controller regulates the generator output power when the wind speed exceeds the rated wind turbine speed. Besides this, it can also be employed to stabilize the wind energy system rotor speed during the transient disturbances. In this article, therefore, a logical pitch-angle controller strategy (in power and speed control modes) has been developed and an interval Type-2 fuzzy logic technique is proposed to design the controller. To evaluate the effectiveness of the Type-2 fuzzy logic–based pitch-angle controller, the simulations have been carried out for severe network faults and fluctuating wind conditions, and the results are compared with conventional proportional–integral and fuzzy logic controller (called as Type-1 fuzzy logic controller). Moreover, some key factors that affect the transient stability of wind generator have also been investigated. The electrical torque and mechanical torque versus rotor speed results are obtained under different pitch-angle conditions, and the concept of stable and unstable electrical–mechanical equilibrium points is established.